Does skills mismatch exist in the TVET sector a Western Mindanao (Region IX) case - Ofianga, Mary Rose P.
Skills mismatch is a condition wherein there is an inequality between the supply and the demand of skills in the labor market. Skills and knowledge are acquired in different ways not just through higher education but also through technical and vocational education and training (TVET). There is an increasing demand by students for the skills provided by the TVET sector in Mindanao. Hence, this study focused on the determination if the skills provided by TVET respond to the needs of the economy in Western Mindanao. To determine if indeed skills mismatch in the TVET sector of the region exists and to identify its causes, the proponent examined the condition of the economy of the region using the Gross Regional Domestic Product (GRDP) and the labor market using employment and unemployment data by sector (agriculture, industry and services). The supply and demand of the TVET sector were also analyzed. The proponent was not able to employ the regression analysis due to the lack of time series data. However, correlation analysis was utilized to determine the relationship of some variables. A case study was also done to supplement the results obtained from the analysis of secondary data. In this study, the proponent found out that skills mismatch exist in Western Mindanao region. This means that the supply of skills do not meet the demand of the labor market. The supply of skills in the TVET sector were mostly on the services sector, knowing that the region has an agricultural economy. Nevertheless, the services sector in the region is fast growing. Moreover, the TVET sector in the region are eyeing for employment abroad rather than responding to the need of the local economy. Hence, the proponent concluded that though skills mismatch exists in the region, it is not that intensive. The proponent was able to draw policy implications and recommendations on this regard to address the causes on skills mismatch in the TVET sector in Western Mindanao.